Do financial reforms help stabilize inequality?. (February 2017) - Christopoulos, Dimitris; McAdam, Peter
Highlights: Explores relationship between financial reforms and income inequality using a panel of 29 countries in 1975–2005. Extend panel unit root tests to allow for the presence of some financial-reform covariates and structural breaks. Gross and net Gini indices follow a unit root process. This picture can change when financial reform indices are accounted for. Gross Gini coefficients are not stabilized by financial reforms; net measures are (more likely to be). Financial reforms enacted in the presence of a strong safety net seem preferable. Abstract: We explore the relationship between financial reforms and income inequality using a panel of 29 countries in 1975–2005. We extend panel unit root tests to allow for the presence of some financial-reform covariates and further suggest an associated but novel, semi-parametric approach. Results demonstrate that although both gross and net Gini indices follow a unit root process, this picture can change when financial reform indices are accounted for. In particular, while gross Gini coefficients are generally not stabilized by financial reforms, net measures are (more likely to be). Thus financial reforms enacted in the presence of a strong safety net would seem preferable.